Role of high-density lipoprotein cholesterol in health and diseases - Brijesh Yadav; Narayan Prasad (Indian Journal of Rheumatology)
Primary function of high-density lipoprotein cholesterol is to reverse transport the cholesterol from extrahepatic cell to liver for its metabolism and excretion. Studies have demonstrated the anti-inflammatory, anti-atherogenic, anti-oxidant, and anti-diabetic property of the high-density lipoprotein cholesterol. Although the exact mechanism still remains unelucidated, high-density lipoprotein cholesterol is a complex of lipids and proteins carrying many associated cargo molecules such as enzymes, signaling molecules, miRNA, which imparts overall functionality of high-density lipoprotein cholesterol for its beneficial health effects. However, the protein and lipids components get transform by the enzymes associated with high-density lipoprotein cholesterol, hyperglycemia, oxidative stressor, and free radicals, leading to qualitative and quantitative alterations in high-density lipoprotein cholesterol (HDLc) and diminishes its beneficial effects. In this review, we have discussed the different property of high-density lipoprotein cholesterol, its function and factors influencing HDLc property in light of anti-inflammatory activity in rheumatoid arthritis and the role of cholesterol-lowering statin drug in enhancing the beneficial effect of high-density lipoprotein cholesterol in different cell types.